(untitled) (Филолошки студии, 2021)
This essay analyses the autobiographical trilogy authored by a Croatian writer mostly known for her children’s stories, Sunčana Škrinjarić (1931-2004). The trilogy consists of the novels Ulica predaka [The Ancestor’s Lane], Ispit zrelosti [The Matriculation Exam], and Bijele strijele [White Arrows], published between 1980 and 2004. I interpret them as feminist Bildungsroman, a genre present both in the West and in the East, tracking the heroine’s venture from the private into public sphere, while downplaying the importance romance and marriage had in the classic, male-centric version of the form. Following a narrative analysis, I discuss Škrinjarić’s portrayal of aesthetic norms and cultural production and outline possibilities of resistance through reading and writing. The third section of the essay engages with the history of Yugoslav feminism and situates Škrinjarić within a recently revised timeline of women’s activism that emphasizes the continuity between the government-supported project of women’s emancipation and second-wave feminism. By combining textual analysis with wider cultural context, I have found that Škrinjarić’s still widely obscure trilogy offers valuable insights into the formation of female identities and possible plots in which we encounter said identities.